Distinct roles for the α, β and γ1 isoforms of protein phosphatase 1 in the outside-in αIIbβ3 integrin signalling-dependent functions - Alrehani, Nawaf; Pradhan, Subhashree; Khatlani, Tanvir; Kailasam, Lavanya; Vijayan, Vinod K. (Thrombosis and Haemostasis, 2013)
Although protein kinases and phosphatases participate in integrin αIIbβ3 signalling, whether integrin functions are regulated by the catalytic subunit of protein phosphatase 1 (PP1c) isoforms are unclear. We show that siRNA mediated knockdown of all PP1c isoforms (α, β and γ1) in 293 αIIbβ3 cells decreased adhesion to immobilised fibrinogen and fibrin clot retraction. Selective knockdown of only PP1cγ1 did not alter adhesion or clot retraction, while depletion of PP1cβ decreased both functions. Unexpectedly, knockdown of PP1cα enhanced αIIbβ3 adhesion to fibrinogen and clot retraction. Protein interaction studies revealed that all PP1c isoforms can interact with the integrin αIIb subunit. Phospho-profiling studies revealed an enhanced activation of mitogen- activated protein kinase (MAPK) p38 in the PP1cα depleted cells. Enhanced adhesive phenotype displayed by the PP1cα-depleted 293 αIIbβ3 cells was blocked by pharmacological inhibition of p38. Conversely, the decreased adhesion of PP1cα overexpressing cells was rescued by the expression of constitutively active p38α or p38γ. Thus, PP1c isoforms have distinct contribution to the outside-in αIIbβ3 signalling- dependent functions in 293 αIIbβ3 cells. Moreover, PP1cα negatively regulates integrin function by suppressing the p38 pathway.
Keywords: Protein phosphatase 1; adhesion; clot retraction; fibrinogen